Early Essential Newborn Care can still be used with mothers who have COVID‐19 if effective infection control measures are applied. (23rd March 2021) - Tran, Hoang Thi; Huynh, Le Thi; Le, Chau Hoang Minh; Nguyen, Vinh Dai; Nguyen, Phuong Thi Thu; Hoang, Diep Thi; Nguyen, Nhan Thi Thanh; Pham, Nga Thi Quynh; Murray, John C. S.; Park, Kidong; Sobel, Howard
Abstract: We describe the first infant born to a woman with COVID‐19 in Vietnam, by Caesarean section at 36 weeks and 5 days of gestation. The mother and baby remained together during their hospital stay and prolonged skin‐to‐skin contact and early and exclusive breastfeeding were achieved. This was in line with the World Health Organization's Early Essential Newborn Care (EENC) recommendations, the national Vietnamese standard of care since 2014. The baby remained virus‐free throughout the 34‐day postpartum follow‐up. Conclusion: The EENC approach can still be used with mothers who have COVID‐19 if effective infection control measures are applied.